Searching for the Institutional Arrangements Towards a New Global Environmental Governance - Moreno-Plata, Miguel (2021)
Over recent decades the planet’s ecosystems have been subjected to severe damage, as a result of their unprecedented exploitation, despite the institutional arrangements generated since the recognition of these environmental problems by the international community. This article examines some theoretical approaches to global governance, looking for answers regarding the interactive processes, institutions and sociopolitical actors immersed in the building of a new world governance. By means of a qualitative methodology, this work analyses the main weaknesses of the current institutional frameworks and the international sectorial organizations on the matters of environment, climate change and sustainable development. It is concluded that a root cause of the problem is the absence of authentic global governance systems to tackle the socioecological crisis, as the actual institutional frameworks consist of a chaotic conglomerate of formal and informal instruments, which lack the effective social and institutional articulation mechanisms needed by the complex, dynamic and interactive nature of the contemporary environmental quandary. The architecture of the new governance systems could be supported upon the multilevel, transversal and transnational integration of the institutional frameworks, as a basis for the reconfiguration of actors, processes and structures of the global environmental governance in the twenty-first century.